Efficacy of triptolide on the apoptosis of tonsillar mononuclear cells from patients with IgA nephropathy. (2nd January 2016) - Yan, Wenzhe; Peng, Youming; Liu, Chan; Ye, Muyao; Chen, Xian; Peng, Xiaofei; He, Liyu; Wang, Jiayi; Liu, Hong; Liu, Fuyou; Zhang, Guangsen
Abstract: Aims : This study aimed to evaluate the extent of apoptosis of tonsillar mononuclear cells (TMCs) derived from patients with IgA nephropathy (IgAN) and the effects of triptolide (TP) on the apoptosis of these TMCs. Methods : TMCs were isolated from tonsillar tissues of patients with IgAN or chronic tonsillitis (control group). Rates of TMCs apoptosis were measured by annexin V-fluorescein isocyanate (FITC)/propidium iodide (PI)-labeled flow cytometry (FCM). Expression levels of Bcl-2 family proteins were quantified by immunohistochemistry of fixed tonsillar sections and Western blot analyzes of TMCs lysates. TMCs from IgAN patients were treated 10, 20, or 30 ng/mL TP for 24 h and then evaluated for viability by the 3-(4, 5-dimethyl-2-thiazolyl)-2, 5-diphenyl-2 H -tetrazolium bromide (MTT) assay, for the percentage of apoptotic cells by FCM, and for the relative expression levels of Bcl-2 family proteins by Western blot analysis. Results : Compared to TMCs from the control group, TMCs from the IgAN group demonstrated lower rates of apoptosis, higher expression levels of the anti-apoptosis proteins Bcl-2 and Bcl-xL, and lower expression levels of the pro-apoptosis protein Bax. Treatment of IgAN patient-derived TMCs with 10, 20, or 30 ng/mL TP for 24 h suppressed the viability and promoted the apoptosis of TMCs in a dose-dependent manner. Western blot analysis revealed a TP dose-dependent decrease in Bcl-2 and Bcl-xL expression levels, in parallel with increased Bax protein levels. Conclusion : TMCs from IgAN patients may be in a state of inhibited apoptosis mediated by Bcl-2 family proteins, which may be reversed by TP treatment.